Effectiveness Of Implementing The Industrial Work Practice Program For State Vocational School Students In DKI Jakarta Province - Nahason Sitohang (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The objective of this research is to evaluate the program of the industrial work practice of SMKN student. The Discrepancy Evaluation Model (DEM) is used in this research supported hy data collection techniques of observation, interview, distribution of questionaires, and related document gathering. Data analysis is carried out in line with aspect to be evaluated (comprises definition, installation, process and product) and the evaluation criteria. The research's findings showed that the program had clearly enough regulation basis, prepared installation by the goverment, good process, and has the differences gap for making correction in the future.